Physiological and biochemical indicators in Norway spruces freshly infested by Ips typographus: potential for early detection methods - Stříbrská, Barbora; Hradecký, Jaromír; Čepl, Jaroslav; Modlinger, Roman; Tomášková, Ivana; Jirošová, Anna (Frontiers in Forests and Global Change, 2023)
Intoduction The bark beetle Ips typographus currently represents the primary pest of Norway spruce (Picea abies) in Central Europe. Early detection and timely salvage cutting of bark beetle-infested trees are functional management strategies for controlling bark beetle outbreaks. However, alternative detection methods are currently being developed, and possible indicators of bark beetle infestation can be assessed through changes in the physiological, biochemical, and beetle-acceptance characteristics of trees. Method This study monitored infested and non-infested Norway spruce trees before and 3 weeks after Ips typographus natural attack. Permanently installed sensors recorded physiological features, such as sap flow, tree stem increment, bark surface temperature, and soil water potential, to monitor water availability. Defensive metabolism characteristics, beetle host acceptance, and attractiveness to trees were monitored discretely several times per season. The forest stand that was later attacked by bark beetles had lower water availability during the 2018–2020 seasons compared to the non-attacked stands. Results After the attack, sap flow and tree stem increment were significantly lower in infested trees than in intact ones, and bark surface temperature moderately increased, even when measured in the inner forest stand from the shadowed side. Infested trees respond to attacks with a surge in monoterpene emissions. In addition, freshly infested trees were more accepted by males in the no-choice bioassays, and a significantly higher number of beetles were caught in passive traps in the first week of infestation. Conclusion The most promising characteristics for early detection methods of bark beetle-infested trees include tree bark temperature measured only in certain meteorological conditions, elevated monoterpene emissions, and significantly high catches in passive traps.